High Fall Risk Associated With Memory Deficit and Brain Lobes Atrophy Among Elderly With Amnestic Mild Cognitive Impairment and Mild Alzheimer’s Disease - Huang, Shuyun; Zhou, Xinhan; Liu, Yajing; Luo, Jiali; Lv, Zeping; Shang, Pan; Zhang, Weiping; Lin, Biqing; Huang, Qiulan; Feng, YanYun; Wang, Wei; Tao, Shuai; et al. (Frontiers in Neuroscience, 2022)
Objectives: To primarily examine the association of memory deficit and increased fall risk, secondly explore the underlying neuroanatomical linkage of this association in elderly with aMCI and mild AD. Methods: In this cross-sectional study, a total of 103 older adults were included (48 cognitive impairment, CI, with aMCI and mild AD). Memory was assessed by the Auditory Verbal Learning Test. Fall risk was evaluated by the Timed Up and Go Test, heel strike angles, and stride speed, which were collected by an inertial-sensor-based wearable instrument. Brain volumes were full-automatic segmented and quantified using AccuBrain® v1.2 from MR images. Multivariable regression analysis was used to examine the extent to the association between memory and fall risk, the association of brain volumes with memory, and fall risk. Results: Compared to CN, participants with aMCI and mild AD had poorer cognitive performance (p<0.001), longer TUG time (p =0.018), smaller hippocampus and medial temporal volumes (p=0.037 and 0.029). In the CI group, compared to good short delayed memory (SDM) performance, elderly with bad SDM performance had longer TUG time, smaller heel strike angles, and slower stride speed. Multivariable regression analysis showed that elderly with poor memory had higher fall risk than relative good memory performance among CI elderly. The TUG time increased by 2.1 seconds, 95% CI, 0.54~3.67; left heel strike angle reduced by 3.22 degrees, 95% CI, -6.05 ~ -0.39; and stride speed reduced by 0.09 m/s, 95% CI, -0.19 ~ -0.00 ) for the poor memory elderly among the CI group. In addition, serious medial temporal atrophy (MTA), small volumes of frontal lobe and occipital lobe were associated with long TUG time and small heel strike angles; small volumes of temporal lobe, frontal lobe, and parietal lobe were associated with slow stride speed. Conclusions: Memory deficit was associated with increased fall risk in the elderly with aMCI and mild AD. The association might be mediated by medial temporal lobe atrophy. Additionally, increased fall risk, tested by TUG time, heel stride angles, and stride speed, might be objective and convenient kinematics markers for dynamic monitoring of both memory function and fall risk.